Characterisation of community-dwelling older adults with poor appetite - Scheufele, Pia; Rappl, Anja; Visser, Marjolein; Kiesswetter, Eva; Volkert, Dorothee (European Journal of Nutrition, 2023)
Purpose: A poor appetite affects up to 27% of community-dwelling older adults in Europe and is an early predictor of malnutrition. Little is known about the factors associated with poor appetite. The present study, therefore, aims to characterise older adults with poor appetite. Methods: As part of the European JPI project APPETITE, data from 850 participants, aged ≥ 70 years of the Longitudinal Ageing Study Amsterdam (LASA) from 2015/16 were analysed. Appetite during the last week was assessed with a five-point scale and dichotomised into "normal" and "poor". Binary logistic regression was used to examine associations between 25 characteristics from 5 domains—physiological, emotional, cognitive, social, and lifestyle—and appetite. First, domain-specific models were calculated using stepwise backward selection. Second, all variables contributing to poor appetite were combined in a multi-domain model. Results: The prevalence of self-reported poor appetite was 15.6%. Fourteen parameters from all five single-domain models contributed to poor appetite and were entered into the multi-domain model. Here, female sex (total prevalence: 56.1%, odds ratio: 1.95 [95% confidence interval 1.10–3.44]), self-reported chewing problems (2.4%, 5.69 [1.88–17.20]), any unintended weight loss in the last 6 months (6.7%, 3.07 [1.36–6.94]), polypharmacy defined as ≥ 5 medications in the past 2 weeks (38.4%, 1.87 [1.04–3.39]), and depressive symptoms (Centre for Epidemiologic Studies Depression Scale without appetite item) (1.12 [1.04–1.21]) were associated with an increased likelihood of having poor appetite. Conclusion: According to this analysis, older people with the characteristics described above are more likely to have a poor appetite.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Aged; Anorexia of ageing; Chewing problems; Depressive symptoms; Polypharmacy; Weight loss

Comparison of appetite assessment methods in older adults from the APPETITE study - Scheufele, Pia; Horner, Katy; Corish, Clare; Visser, Marjolein; Rappl, Anja; Mullen, Brian; Quinn, Anna; Gonnelli, Federica; Bozzato, Matteo; Volkert, Dorothee (Appetite, 2025)
Poor appetite is an important health concern in older adults. Numerous methods exist for appetite assessment, without a consensual gold standard. This study aims to compare Simplified Nutritional Appetite Questionnaire (SNAQ) and two single-item appetite questions with appetite ratings from visual analogue scales (VAS) and energy intake (EI). In 126 community-dwelling adults aged ≥65 years from the APPETITE trial, appetite was assessed using SNAQ, SNAQ 1st item, Center for Epidemiologic Studies-Depression scale (CES-D) 2nd item and using VAS appetite ratings (fasting, 0, 30, 60, 120, 180 min post-breakfast, post-lunch) and EI (ad libitum lunch) in a test meal setting. Spearman correlations were calculated between SNAQ, single-items, VAS-fasting, and EI. Differences in VAS-fasting and EI between normal and poor appetite groups (based on SNAQ, single-items) were examined using Mann-Whitney-U-test. Repeated measures Generalized Linear Models were used to compare all VAS ratings across the test morning and post-breakfast response ratings with VAS-fasting as a covariate between appetite groups. SNAQ score was correlated with VAS-fasting (r = 0.26, p < 0.001) and EI (r = 0.22, p < 0.05). VAS-fasting was lower in the SNAQ-based poor appetite group (p = 0.01). Time/group interaction effects (SNAQ, ηp2 = 0.02; CES-D-item, ηp2 = 0.02) for all VAS ratings, and group (SNAQ-item, ηp2 = 0.04) and interaction effects (CES-D-item, ηp2 = 0.03) for post-breakfast ratings were observed (p < 0.05, respectively). SNAQ identified differences in VAS-fasting, possibly reflecting processes related to the drive to eat, while the two single-items identified appetite differences in response to a standardised breakfast. Different methods appear to capture different aspects of appetite, which should be considered when choosing an assessment method.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Aged; Appetite; Appetite assessment; Energy intake; Simplified nutritional appetite questionnaire; Visual analogue scale

Dietary characteristics of community-dwelling older adults with poor appetite: a cross-sectional analysis - Scheufele, Pia; Rappl, Anja; Visser, Marjolein; Kiesswetter, Eva; Volkert, Dorothee (Age and Ageing, 2024)
Rationale: Poor appetite is considered a key factor in the development of malnutrition, a link that can be explained by alterations in dietary intake. Given the limited data on dietary characteristics in community-dwelling older adults with poor appetite, the present study aimed to examine whether poor appetite is associated with lower nutrient intake and more unfavourable food choices. Methods: In 569 participants of the Longitudinal Aging Study Amsterdam aged ≥70 years appetite was assessed using the Simplified Nutritional Appetite Questionnaire and dichotomised into normal (>14) and poor (≤14). Intake of energy, 19 nutrients, 15 food groups, the Dutch Healthy Diet Index 2015 (DHD15) and Mediterranean Diet Score (MDS) were calculated from a food frequency questionnaire. Dietary differences between appetite groups were examined using Mann–Whitney U test and binary logistic regression adjusted for potential confounders. Results: Mean age was 78 ± 6 years and 52% were female. Appetite was poor in 12.5% of participants. Energy intake was 1951 (median; quartiles 1–3: 1,653–2,384) kcal/day with no difference between appetite groups. Poor appetite was associated with lower intake of protein (OR 0.948, 95%CI 0.922–0.973), folate (0.981, 0.973–0.989), zinc (0.619, 0.454–0.846), vegetables (0.988, 0.982–0.994) and lower scores of DHD15 (0.964, 0.945–0.983) and MDS (0.904, 0.850–0.961), as well as higher intake of carbohydrates (1.015, 1.006–1.023), and vitamins B2 (4.577, 1.650–12.694) and C (1.013, 1.005–1.021). Conclusions: Community-dwelling older adults with poor appetite showed poorer diet quality with a lower intake of protein, folate, zinc and vegetables, compared with those reporting normal appetite and should be advised accordingly.
CRIS-Team Scopus Importer:2024-05-24
Keywords: anorexia of ageing; diet quality; malnutrition; older adults; poor appetite